Transcatheter mitral valve replacement or repair for secondary mitral regurgitation: a propensity score‐matched analysis. (8th March 2023) - Ludwig, Sebastian; Kalbacher, Daniel; Ali, Walid Ben; Weimann, Jessica; Adam, Matti; Duncan, Alison; Webb, John G.; Windecker, Stephan; Orban, Mathias; Giannini, Cristina; Coisne, Augustin; Karam, Nicole; et al.
ABSTRACT: Aims: This study aimed to compare outcomes after transcatheter mitral valve replacement (TMVR) and mitral valve transcatheter edge‐to‐edge repair (M‐TEER) for the treatment of secondary mitral regurgitation (SMR). Methods and results: The CHOICE‐MI registry included 262 patients with SMR treated with TMVR between 2014 and 2022. The EuroSMR registry included 1065 patients with SMR treated with M‐TEER between 2014 and 2019. Propensity score (PS) matching was performed for 12 demographic, clinical and echocardiographic parameters. Echocardiographic, functional and clinical outcomes out to 1 year were compared in the matched cohorts. After PS matching, 235 TMVR patients (75.5 years [70.0, 80.0], 60.2% male, EuroSCORE II 6.3% [interquartile range 3.8, 12.4]) were compared to 411 M‐TEER patients (76.7 years [70.1, 80.5], 59.0% male, EuroSCORE II 6.7% [3.9, 12.4]). All‐cause mortality was 6.8% after TMVR and 3.8% after M‐TEER at 30 days ( p  = 0.11), and 25.8% after TMVR and 18.9% after M‐TEER at 1 year ( p  = 0.056). No differences in mortality after 1 year were found between both groups in a 30‐day landmark analysis (TMVR: 20.4%, M‐TEER: 15.8%, p  = 0.21). Compared to M‐TEER, TMVR resulted in more effective mitral regurgitation (MR) reduction (residual MR ≤1+ at discharge for TMVR vs. M‐TEER: 95.8% vs. 68.8%, p  < 0.001), and superior symptomatic improvement (New York Heart Association class ≤II at 1 year: 77.8% vs. 64.3%, p  = 0.015). Conclusion: In this PS‐matched comparison between TMVR and M‐TEER in patients with severe SMR, TMVR was associated with superior reduction of MR and superior symptomatic improvement. While post‐procedural mortality tended to be higher after TMVR, no significant differences in mortality were found beyond 30 days. Abstract : Transcatheter replacement versus repair for secondary mitral regurgitation (SMR). BMI, body mass index; eGFR, estimated glomerular filtration rate; EROA, effective regurgitant orifice area; H/o, history of; LVEDV, left ventricular end‐diastolic volume; LVEF, left ventricular ejection fraction; M‐TEER, mitral valve transcatheter edge‐to‐edge repair; NYHA, New York Heart Association; TMVR, transcatheter mitral valve replacement; TAPSE, tricuspid annular plane systolic excursion; TR, tricuspid regurgitation.